Patterns of Antimicrobial Resistance Among Intensive Care Unit Patients of A Private Medical College Hospital in Dhaka (Bangladesh Journal of Medicine, 2015)
Because of importance of Hospital acquired infections (HAIs), it is critical to conduct surveillance studies to obtain the required data about the regional microorganisms and their susceptibility to antibiotics. This study to investigate antimicrobial resistance pattern among Intensive Care Unit (ICU) patients in a private medical college hospital setup. In a cross sectional study, 100 specimens from patients admitted in the ICU who had signs or symptoms of nosocomial infection were collected from 2012 - 2013. For each patient, samples of blood, urine, tracheal aspirate, sputum, wound swab, pus, and endotracheal tubes were obtained, cultured and analyzed with antibiogram. The most common primary diagnosis were aspiration pneumonia (49%) and UTI (20%) respectively. The most common locations for infection were tracheal aspirate (54%). The most frequent gram negative microorganisms derived from samples were Acinetobacter spp (29%), Klebsiella spp (26%) and Pseudomonas spp (18%). Klebsiella spp, Acinetobacter spp and Pseudomonas spp were most common resistant organisms among all. Klebsiella spp were resistant against Ceftriaxone (84.6%), Ceftazidime (82.6%), Amikacin (46.1%), Gentamicin (66.6%) and Quinolones (65-66.6%) respectively. Acinetobacter spp were resistant against Ceftriaxone (85%), Ceftazidime (88.8%), Cefotaxime (85.7%), Meropenem (79.3%),Amikacin (86.2%), Gentamicin (84.5%) and Quinolons (86.2-89.2%) respectively. Pseudomonas spp were resistant against Ceftriaxone (70.5%), Ceftazidime (66.6%), Amikacin (68.7%), Gentamicin (58.8%), Meropenem (52.9%) and Quinolones (81.2-86.6%) respectively. Meropenem was the most sensitive antibiotic against Klebsiella spp (84.6%) but Cotrimoxazole in case of Acinetobacter spp (60%) respectively. Escherichia coli were mostly isolated from urine, which was sensitive to Amikacin (73.3%) and Meropenem (86.6%) respectively. Gram-negative pathogens obtained from ICU patients in our settings show high resistance to antibiotics. Regular monitoring of the pattern of resistance of common pathogens in the ICUs is essential to up-to-date the use of rational antibiotics regiments.Bangladesh J Medicine Jul 2014; 25 (2) : 47-51